Characterization and heat transfer effect of graphene nanoflakes on polymerase chain reaction - Rasheed, Abdul Khaliq (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Liquids which contain nano-meter sized particles, also known as nanofluids are well known for their enhanced thermal conductivity over base fluids. Nanofluids have been investigated with several heat transfer applications including few molecular biology tools. Polymerase chain reaction (PCR) is one of the most fundamental tools in medicine and molecular biology which needs further enhancement of its efficiency. Recently, the addition of few metallic, oxide and carbon nanotubes based nanofluids resulted in excellent enhancement in efficiency and specificity of PCR. A preliminary study was conducted to investigate the effect of Al2O3, Al2O3·TiO2 nanoparticles and graphene nanoflakes (GNFs) addition on PCR. The efficiency of PCR was enhanced by ~10 folds with the addition of 0.01wt% of GNFs. Whereas Al2O3 results in enhancement of ~6 folds whereas Al2O3·TiO2 nanoparticles exert inhibitory effect with the addition of similar concentrations of nanofluids. Owing to high yield of the DNA product using GNFs than Al2O3, Al2O3·TiO2 nanoparticles in preliminary experiments and also because of the unique physical and thermal properties of GNFs, detailed PCR experimental analyses were performed with GNFs. The thermal conductivity of GNFs nanofluids was measured and found to be in agreement with those of literature. The PCR results strongly suggest that GNFs is a potential enhancer of PCR efficiency. The PCR enhancements are strongly GNFs concentration dependent. Furthermore, GNFs yields product equivalent to positive control with reducing the PCR cycles up to ~65%. The experiments using supernatant of GNFs strongly suggests that the PCR enhancement might be mainly because of the superior thermal conductivity effect rather than the GNFs itself. Numerical simulation results obtained using computational fluid dynamics strongly suggest that the presence of GNFs renders faster heat transfer than TiO2 nanoparticles. The heating steps (denaturation and extension) and the cooling step (annealing) of PCR were simulated individually. The temperature contours suggests that the GNFs addition renders improved heat transfer in all the three steps. This observation also advocates that the higher concentration of nanoparticles and down-scaling of their size will eventually help better heat transfer through the PCR tube. The findings of this research might be useful in developing GNFs as a prominent PCR enhancer. The recommendation and suggestions can act as a basis for a focused research in future.